Review: Aktivitas Antiinflamasi Ekstrak Etanol Tanaman Patah Tulang (Euphorbia Tirucalli L.) - Octavian, I Putu Yudi (Program Studi Akuntansi IKOPIN, 2022)
Fracture plant branch extract has potential as a medicinal plant which has been detected to have secondary metabolite compounds that can provide antiinflammatory effects. The compounds contained in the methanol extract of fracture branches were flavonoids, tannins and saponins, while the chloroform extract was only detected positive for alkaloids. The purpose of this study was to examine the anti-inflammatory activity of the ethanol extract of the fracture plant against edema caused by carrageenan in rats' feet. In this review article, we will provide information and discuss the anti-inflammatory activity of fracture plants along with the suspected class of compounds that play a role in inhibiting this inflammation).